Perspectives of psychiatrists on Mental Health Care Act, 2017: An in-depth pilot survey - Astha; Shruti Srivastava; Indira Sharma (Industrial Psychiatry Journal)
Background: The Mental Health Care Act, 2017 (MHCA, 17) was passed through both houses of the parliament. The Indian Psychiatric Society through its Patient’s Rights Task Force committee has been deliberating various rounds of discussion at levels of stakeholders, mental health professionals, and patients’ perspective. However, a scarce budget for mental health services, lack of trained mental health professionals, and poor infrastructure and logistics pose a challenge for this new act as still there is a lack of awareness of different provisions of MHCA at the administrative, judiciary, and public levels. Aim: The present study was undertaken to address the perspectives of psychiatrists related to MHCA,2017 its provisions. Materials and Methods: A self-administered questionnaire was designed to gather information on awareness about MHCA, 2017. The responses were collected from the member psychiatrists of Indian Psychiatric Society in a google form including the suggestions regarding amendments in MHCA, 2017. Results: 22.6% of participants were using MHCA in clinical practice completely, and 20.2% did not use it all. 52.4% stated that they are using it partly. Capacity assessment of the person suffering from mental illness was done by 52.4% of participants in day-to-day clinical practice. 35.7% denied assessing it. With respect to section 309 IPC, 31% were registering and managing suicide attempts as medico legal cases and 63.1% as non-MLC cases. 54.2% of the participants were not aware about medical insurance for mental health. The qualitative data suggest the act should be simplified including relaxation in provisions of minor, capacity assessment and ensure active functioning of various authorities. Conclusions: Amendments are required in MHCA, 2017 taking into cognizance the opinions from various practicing psychiatrists who are facing hurdles in routine clinical practice.